Mobile-based Electronic Health Card Application using Realtime Push Notification - Husna, Fauziatun; Suendri, Suendri (Sistemasi: Jurnal Sistem Informasi, 2024)
The Healthy Way Card (KMS) is a valuable tool for documenting and tracking the growth and development of children between the ages of 0 and 5 years. The aim of this research is to make it easier for cadres and parents to see the development of toddlers as well as reminders of posyandu activity schedules in real time. This research uses Firebase Realtime Database for storing toddler data and Firebase Storage for storing media/photos. Use of Java and Android Studio as programming languages. The Waterfall system development method is also used. Push Notification is divided into 2 privileges, namely Broadcast for routine posyandu information which is sent to all users and Private which is pushed to each user's account for the development of toddlers after activities. The Towards Healthy Card Application System has a multiplatform, namely Mobile and Web. The system used can run well. The system can be accessed by several users so that it can be used to record data on toddler development, as well as obtain information on posyandu activities in real time. Thus, from the test results, the system can display growth and development graphs, immunization graphs, weight graphs, from all these graphs you can see toddler development data.